Pembangunan Desa Berkembang Sebagai Desa Sejahtera dan Mandiri dalam Perspektif Administrasi Pembangunan dan Dynamic Governance - Larasati, Nabilla; Ria, Catur Ajeng Kartika; Kusnan, Kusnan (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
The current development is not only centeren in cities, but has also entered the countryside in every region in Indonesia. The increasing of welfare and quality of life for villager is a goal of implementating rural development is on the Law no. 6/2014. The Concept of Development Administration and the concept of dynamic governance can be used as a basis for reviewing the development of prosperous and independent village, the village named is Ngroto Village. Library research method used in this study, which means that the author conduct a literature review. Meanwhile, the focus of this study is village development and the commitment of the villager in Ngroto Village. As a result, the village can be used as a state economic circulation (money) as long as it creates economic circulation (money) in the village. Then, the synergy must be estabilished between government and the villager in Ngroto Village to realize prosperous and independent village. Thus, poverty and ignorance that been connoted to villager can be minimized or even eliminated.